Educational Assessment: Parental Economics and the High Incidence of Learning Loss - Tjilen, Alexander Phuk; Rediani, Ni Nyoman (Indonesian Journal of Educational Research and Review, 2023)
Loss of specific or general knowledge and skills, commonly referred to as ‘learning loss,’ continues to be a concern in Indonesia. This research aims to analyze the relationship between economic factors and the incidence of learning loss among students. The primary objective is to gain a deeper understanding of how economic aspects can impact students’ learning outcomes. The research employed an ex-post facto research design, which involves data collection after the event being studied. The study involved 30 fifth-grade elementary school students and 30 parents as participants. Data was collected through methods such as observation, interviews, questionnaires, and tests. The data analysis approach in this research assumes linearity. The research results highlight a significant correlation between parents’ economic conditions and learning loss, underscoring a critical issue in the education sector. With a significance value (Sig value) less than 0.05, it can be concluded that parents’ economic backgrounds play a pivotal role in influencing the extent of learning loss. Learning loss, often attributed to factors like students participating in family economic activities such as forest labor or fishing, can have adverse effects on the quality of education and human resource development. Consequently, addressing this issue requires concrete actions, including providing support to affected students and fostering a more inclusive educational environment.